Loop nerve graft prefabrication for peripheral nerve defect reconstruction - ŞİRVANCI, SERAP (My University, 2022)
BACKGROUND: Delayed autologous nerve graft reconstruction is inevitable in devastating injuries. Delayed or prolonged repair time has deleterious effects on nerve grafts. We aimed improving and accelerating nerve graft reconstruction process in a rat long nerve defect model with loop nerve graft prefabrication particularly to utilize for injuries with tissue loss. METHODS: Twenty-four Sprague-Dawley rats were allocated into three groups. 1.5 cm long peroneal nerve segment was excised, reversed in orientation, and used as autologous nerve graft. In conventional interpositional nerve graft group (Group 1), nerve defects were repaired in single-stage. In loop nerve graft prefabrication group (Group 2), grafts were sutured end-to-end (ETE) to the proximal peroneal nerve stumps. Distal ends of the grafts were sutured end-to-side to the peroneal nerve stumps 5 mm proximal to the ETE repair sites in first stage. In second stage, distal ends of the prefabricated grafts were transposed and sutured to distal nerve stumps. In staged conventional interpositional nerve graft group (Group 3), grafts were sutured ETE to proximal peroneal nerve stumps in first stage. Distal ends of the grafts and nerve stumps were tacked to the surrounding muscles until the final repair in second stage. Followup period was 4 weeks for each stage in Groups 2 and 3, and 8 weeks for Group 1. Peroneal function index (PFI), electrophysiology, and histological assessments were conducted after 8 weeks. P<0.05 was considered significant for statistical analysis. RESULTS: PFI results of Group 1 (−22.75±5.76) and 2 (−22.08±6) did not show statistical difference (p>0.05). Group 3 (−33.64±6.4) had a statistical difference compared to other groups (p<0.05). Electrophysiology results of Group 1 (16.19±2.15 mV/1.16±0.21 ms) and 2 (15.95±2.82 mV/1.17±0.16 ms) did not present statistical difference (p>0.05), whereas both groups had a statistical difference compared to Group 3 (10.44±1.96 mV/1.51±0.15 ms) (p<0.05). Axon counts of Group 1 (2227±260.4) and 3 (2194±201.1) did not have statistical difference (p>0.05), whereas both groups had significantly poor axon counts compared to Group 2 (2531±91.18) (p<0.05). CONCLUSION: Loop nerve graft prefabrication improved axonal regeneration without delay. Loop prefabrication can accelerate prolonged regeneration time for the injuries indicating a delayed nerve reconstruction. Higher axon counts derived with loop nerve prefabrication may even foster its investigation in immediate long nerve defect reconstructions in further studies.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; ACİL TIP; Klinik Tıp; Klinik Tıp (MED); EMERGENCY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Acil Tıp Hizmetleri; Emergency Medical Services; Loop nerve prefabrication; nerve graft; nerve injury; nerve; TO-SIDE NEURORRHAPHY; SCHWANN-CELLS; REGENERATION; REPAIR; STRATEGIES; LENGTH; Loop nerve prefabrication; nerve graft; nerve injury; nerve repair.